2021
DOI: 10.20944/preprints202109.0010.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning Algorithms Provide Greater Prediction of Response to Scs Than Lead Screening Trial: A Predictive AI-Based Multicenter Study

Abstract: Persistent Pain after Spinal Surgery can be successfully addressed by Spinal Cord Stimulation (SCS). International guidelines strongly recommend that a lead trial be performed before any permanent implantation. Recent clinical data highlight some major limitations of this approach. First, it appears that patient outcomes, WITH OR WITHOUT lead trial, are similar. In contrast, during trialing, infection rate drops drastically within time and can compromise the therapy. Using composite pain assessment experience … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Traditional machine learning algorithms mainly include two steps: feature extraction and classification. In the part of feature extraction, this study selects five most advanced global algorithms for texture representation, namely local binary patterns (LBPs) [ 2 ], local phase quantization (LPQ) [ 12 ], gray-level co-occurrence matrix (GLCM) [ 3 ], histogram of oriented gradient (HOG), and oriented fast and rotated brief (ORB) [ 4 ]. The feature dimensions of the five feature descriptors are shown in Table 3 .…”
Section: Model Experiments and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional machine learning algorithms mainly include two steps: feature extraction and classification. In the part of feature extraction, this study selects five most advanced global algorithms for texture representation, namely local binary patterns (LBPs) [ 2 ], local phase quantization (LPQ) [ 12 ], gray-level co-occurrence matrix (GLCM) [ 3 ], histogram of oriented gradient (HOG), and oriented fast and rotated brief (ORB) [ 4 ]. The feature dimensions of the five feature descriptors are shown in Table 3 .…”
Section: Model Experiments and Results Analysismentioning
confidence: 99%
“…The second type is the automatic segmentation or grading research directly based on the intervertebral foramen. Reference [ 11 ] realized the segmentation by detecting the center line of the vertebral body and the main boundary points of the intervertebral foramen; [ 12 ] used the AdaBoost detection algorithm and iterative normalization segmentation algorithm to detect MRI vertebral body images and locate and segment them at the same time; [ 13 ] realized the modeling and segmentation of spine and intervertebral foramen based on two scales by representing the global spine shape in a continuous local vertebral coordinate system and modeling the individual vertebrae as a triangular surface network; [ 14 ] used the super-pixel segmentation method to achieve an accuracy of 98.52% in the image location and benign and malignant classification of intervertebral foramen stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was proposed that machine algorithms be used to predict response to SCS, based on clinical outcomes from 103 implanted patients. 53 , 54 The authors found that the sensitivity of the screening trial was greater than the machine-learning model (100% vs 83.3%), while specificity was significantly lower for the screening trial than the machine learning trial (33.3% vs 66.7%). Machine-learning and statistical models could be considered in future trials to delineate SCS-screening trial utility.…”
Section: Biasmentioning
confidence: 99%
“…Chronic pain is defined by the International Association for Study of Pain (IASP) as « an unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage » [1] lasting more than 3 months [2]. By affecting more than 30% of population worldwide [3], chronic pain leads to economic burden and has dramatic impact on biological, psychological, sociological factors resulting in poor quality of life [4][5][6]. While medical care focused in pain perception, psychological and functional disability should be considered [6].…”
Section: Introductionmentioning
confidence: 99%
“…By affecting more than 30% of population worldwide [3], chronic pain leads to economic burden and has dramatic impact on biological, psychological, sociological factors resulting in poor quality of life [4][5][6]. While medical care focused in pain perception, psychological and functional disability should be considered [6]. It has been clearly demonstrated that pain interferes with sensorimotor control [7][8][9][10][11], and more especially with postural control [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%